2009
DOI: 10.4103/0028-3886.53289
|View full text |Cite
|
Sign up to set email alerts
|

Retained surgical sponge in differential diagnosis of paraspinal soft-tissue mass after posterior spinal surgery: Report of eight cases

Abstract: Retained paravertebral surgical sponges are seldom reported due to medicolegal implications. Awareness of this complication among neurosurgeons and radiologists is essential to avoid unnecessary morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…After surgery, the body can react to foreign bodies such as retained sponges in two ways: (1) exudative tissue reaction which leads to acute abscess formation, and (2) aseptic fibrous tissue reaction, which involves slow adhesion formation such as encapsulation and granuloma formation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, the body can react to foreign bodies such as retained sponges in two ways: (1) exudative tissue reaction which leads to acute abscess formation, and (2) aseptic fibrous tissue reaction, which involves slow adhesion formation such as encapsulation and granuloma formation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These osteolytic changes with marginal sclerosis may be evidence of the benign nature of the lesion and may be specific for gossypiboma around the lamina. MRI usually shows a well-defined mass with a fibrous capsule that exhibits low-signal intensity on T1-weighted imaging and high-signal intensity on T2-weighted imaging within the centre of the lesion and low-signal intensity mimicking a paraspinal abscess [2,4-7,9,10]. Only three cases were heterogeneous on T2-weighted imaging [1,3,8].…”
Section: Discussionmentioning
confidence: 99%
“…Without the marker, as shown in the present case, the level of difficulty in making the diagnosis of gossypiboma skyrockets. In addition, only approximately 50 cases have been reported in the paraspinal location1246791315), and most of the literature has described varying radiologic features in these cases. However, there are some salient radiologic features that can be used to diagnose a gossypiboma.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports have demonstrated that the clinical symptoms associated with gossypibomas were well treated by complete removal of the masses12479121315). However, the clinical symptoms associated with gossypibomas may not be prominent, especially in chronic gossypibomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation